ChemInform Abstract: Protein Nanotechnology: Research, Development, and Precaution in the Food Industry. Issue 26 (6th June 2013) - Matsuda, Masami; Hunt, Geoffrey; Kuboki, Yoshinori; Ogino, Toshio; Fujisawa, Ryuichi; Watari, Fumio; Sammons, Rachel L.
Abstract Review: 50 refs.